Pengembangan Aplikasi Augmented Reality Clothing untuk Meningkatkan Minat Beli Konsumen terhadap Bisnis Clothing Line Kyouka - Haechal Abdillah Suhendar; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Building and developing a clothing brand business to become a huge business is not easy. Clothing brand kyouka is a clothing brand business that has not been formed for a long time. The challenge of creating a clothing brand business is caused not only by competitors, but also by the difficulties of a business in delivering its items to its intended consumers. Good product marketing is one of the determining factors for a business's development, and in this digital era, marketing via social media has become a demand. According to the survey, 45 percent of social media users in Indonesia buy products they see on the Instagram platform, which has 61 million users. An augmented reality application based on social media filters will be built to advertise the Kyouka brand clothes company product based on these issues. The project is being developed on the Spark AR platform, which is an augmented reality filter platform that can be easily connected to social media platforms like Instagram and Facebook via the FixTargetTracker function. The development's outcomes are expected to boost the brand's image and increase consumer interest in Kyouka clothes. Software Testing will be used to assess the application's performance and usefulness for clothing product that have been given augmented reality. The test earned a 100% application on validation test, results from 39 respondents' usability testing got a value of 4.31 as well as increased interest up to 270 consumers, which is a very good result, and the UEQ benchmark results where the attractiveness aspect receives a value of 1.98, perspicuity receives a value of 1.73, efficiency receives a value of 1.71, dependability receives a score of 1.48, stimulation receives a score of 1.70, and novelty receives a score of 1.74, where the benchmark findings were highly.